Implementation of IPsec-VPN Tunneling using GNS3 - Fatimah A. Salman (Institute of Advanced Engineering and Science, 2017)
Virtual private networks (VPN) are used by remote clients to securely connect to company networks. This paper deals with Site-to-site IPsec-VPN that connects the company intranets. IPsec-VPN network is implemented with security protocols for key management and exchange, authentication and integrity which implemented using GNS3 Network simulator. The testing, verification analyzing of data packets of the network is done using both PING tool and Wireshark.